Comparison of Tooth Discoloration Induced by Calcium-Enriched Mixture and Mineral Trioxide Aggregate - Rouhani, Armita; Akbari, Majid; Farhai-faz, Aida (Iranian Endodontic Journal, 2016)
Introduction: The aim of this in vitro study was to evaluate the tooth discoloration induced by calcium-enriched mixture (CEM) cement and mineral trioxide aggregate (MTA). Methods and Materials: Forty five endodontically treated human maxillary central incisors were selected and divided into three groups (n=15) after removing the coronal 3 mm of the obturating materials. In the MTA group, white MTA plug was placed in pulp chamber and coronal zone of the root canal. In CEM cement group, CEM plug was placed in the tooth in the same manner. In both groups, a wet cotton pellet was placed in the access cavity and the teeth were temporarily sealed. After 24 h the teeth were restored with resin composite. In the negative control group the teeth were also restored with resin composite. The color change in the cervical third of teeth was measured with a colorimeter and was repeated 3 times for each specimen. The teeth were kept in artificial saliva for 6 months. After this period, the color change was measured again. Data were collected by Commission International de I’Eclairage’s L*a*b color values, and corresponding ΔE values were calculated. The results were analyzed using the one-way ANOVA and post-hoc Tukey’s test with the significance level defined as 0.05. Results: There was no significant differences between CEM group and control group in mean discoloration. The mean tooth discoloration in MTA group was significantly greater than CEM and control groups (P<0.05). Conclusion: According to the result of the present study CEM cement did not induce tooth discoloration after six months. Therefore it can be used in vital pulp therapy of esthetically sensitive teeth. Keywords: Calcium-Enriched Mixture; Dental Cements; Mineral Trioxide Aggregate; Tooth Discoloration; Vital Pulp Therapy